PENGEMBANGAN MEDIA TURBAYA (MINIATUR BUDAYA) PADA PEMBELAJARAN TEMATIK TEMA INDAHNYA KERAGAMAN DI NEGERIKU KELAS IV SD - Annisa Umairoh Brutu; Beta Rapita Silalahi (STKIP Subang, 2023)
This research aims to describe the process of developing turbaya media (cultural miniatures) and to describe whether or not turbaya media (cultural miniatures) are suitable for thematic learning on the theme of the beauty of diversity in my country for class IV MIS Muhajirin students. This research is a type of research and development using the ADDIE model. The subjects in the research were media expert validators and material expert validators. The object of this research is turbaya media (cultural miniatures) in thematic learning on the theme of the beauty of diversity in my country in fourth grade elementary school. The instrument used in this research is a questionnaire. The data analysis techniques used in this research are qualitative descriptive and quantitative descriptive. Based on data analysis obtained through validity testing of material experts and media experts, validation results by material experts (lecturers) obtained 83%, and material experts (teachers) obtained 85% in the very good/valid category, validation results by media experts obtained 95% with a very good/valid category. Based on the data obtained, it can be concluded that the turbaya media (cultural miniatures) in thematic learning on the theme of the beauty of diversity in my country developed by researchers is stated to be very good for use as media in the learning process